SYNTHESIS OF BAND-PASS FILTER WITH THE HELP OF SCHEME FUNCTION WITH COMPREHENSIVE COEFFICIENTS - A. V. Bondarenko; V. V. Reznichenko; V. I. Mozhar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a construction method of arithmetically frequency symmetric band-pass filter on the basis of frequency conversion that results in scheme function with comprehensive coefficients. Methodology of its realization with the help of a digital filter is proposed in the paper.